A microfluidic chip based ratiometric aptasensor for antibiotic detection in foods using stir bar assisted sorptive extraction and rolling circle amplification. Issue 8 (14th March 2019) - He, Liyong; Shen, Zhipeng; Cao, Yuting; Li, Tianhua; Wu, Dazhen; Dong, Youren; Gan, Ning
Abstract : A ratiometric and sensitive microfluidic chip based aptasensor was developed for antibiotic detection with kanamycin (Kana) as a model analyte. Abstract : A ratiometric and sensitive microfluidic chip based aptasensor was developed for antibiotic detection with kanamycin (Kana) as a model analyte. A novel stir bar assisted sorptive extraction and rolling circle amplification strategy was designed to largely amplify the signal and overcome complex matrix interference in food samples. The detection mechanism was as follows: firstly, many duplex DNA probes (a single-stranded DNA as a primer hybrid with an aptamer sequence) were modified on a stir bar. In the presence of Kana, the probes on the bar could specifically capture Kana and release the primer to trigger RCA in the presence of a circular DNA template (CDT). As the reaction proceeds, the amount of CDT decreased and the number of RCA products increased. It is worth mentioning that they can be efficiently separated and detected using a microfluidic chip. The signal ratio of RCA products and CDT ( I R / I C ) can be employed to qualify Kana in a wide linear range from 0.8 pg mL −1 to 10 ng mL −1 with a low detection limit of 0.3 pg mL −1 . This method exhibited excellent sensitivity and selectivity and can obviously reduce the matrix interference through a ratiometric strategy combined with stir bar extraction. The aptasensor was successfully tested in milk and fish samples, confirming that it can be applied for on-site quantitation of antibiotic residues in foods.